The Survey of knowledge, attitude and practice of female hairdressers in Yazd about diseases related to hairdressing profession in 1391 - MT ghaneian; AH mehrparvar; T jasemizad; F mansuri; H selselehvaziri; F zare (طب کار)
Background: One of the ways of transmission of infectious diseases is person to person transmission which hairdressers have an important role in this field. The aim of this study was to determine the knowledge, attitude and practice of female hairdressers about health and diseases related to hairdressing profession in 1391 in Yazd. Methods: This study was a descriptive study that was done randomly on 60 female hairdressers (12% of total female hairdressers in Yazd). The tool of gathering data was a questionnaire that its reliability and validity was determined and after completing, was analyzed by using SPSS 16 and Excel. Results: Demographic data revealed that most hairdressers were less than 30 years old, diploma and have the experience more than 10 years. The results also showed that the age has not significant difference with the knowledge, attitude and performance of hairdressers (P>0.05), education level has a significant difference only with attitude. Work experience has a significant difference with attitudes and knowledge (P0.05). Conclusion: The results of this study showed that the hairdressers have high knowledge, attitudes and performance.